Recycling of organic wastes using locally isolated lignocellulolytic strains and sustainable technology - Adebayo, Opatokun Suraj; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (Springer Japan, 2015)
The magnitude and nature of the waste generated across different borders have prompted the need for an appraisal of the conventional method of waste collection and the landﬁll or incineration that are unsustainable due to their high cost and impact on the environment and public health. This study focuses on the recycling of organic wastes (food waste and yard trimmings) using four isolated fungal strains in an experimental setup that simulates sustainable low-technology treatment for the production compost. Separated food and yard trimmings were composted using Phanerochaete chrysosporium, Lentinus tigrinus, Aspergillus niger and Penicillium sp. in two adopted systems (open and closed) based on a solid-state bioconversion process. The results were obtained at p B 0.05 after ten harvests indicating a pH range of 5.68–8.82, an organic weight loss of 11.92 % and a carbonto-nitrogen (C/N) ratio range of 16.99–18.20 for the open system of the compost. The closed system indicated a relatively lower value of C/N ratio, which is 8.60–13.38 and an organic weight loss of 8.92 % at a pH range of 5.68–7.30. The germination index, ranging between 53–105 and 49–122 %, and the electrical conductivity ranging between 2.57–3.17 and 2.72–2.95 mS/dm for the open and closed systems, respectively, were used to evaluate the toxicity and stability of the compost produced. The technology adopted in this study indicates the viability of the process of the large-scale production of biofertilizer with the C/N ratio of\25 and the signiﬁcance of the germination index values of[100 % at harvest.